Extended Mathematical Connections among Pre-Service Mathematics Teachers: A Systematic Literature Review - Alim Wicaksono; Al Jupri; Tia Purniati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Mathematical connection is considered one of essential aspect to learn mathematics. Framework that extends this connection has become a trend among scholars in many parts of the world especially. Therefore, this research is to provide a comprehensive literature review about extended mathematical connection among pre-service mathematics teacher. Utilizing PRISMA flow diagram, this research 15 articles from a credible source that published within 2017-2026. Based on the database, there are 154 registers paper founded. The articles were going through identification stage which removed 43 duplicated. The screening process was conducted that exclude 89 papers based on inclusion-exclusion criteria. The included articles were examined the eligibility and accessibility which resulted in 15 papers. Studies were analyzed by years, mathematical topics, mathematical connection challenges, and the learning implication. The finding of the research highlight that extended mathematical connection research has risen in the past three years with qualitative as a dominant methods and various mathematical topics such as algebra, geometry, and arithmetic. There is significant gap between university mathematics and school curriculum resulting in low different representation connection and relied on procedural knowledge. Extended Mathematical connection serves as a tool to enhance conceptual understanding, specific types of connection, and learning experiences.